Concepcion : an immigrant family's fortunes - Samaha, Albert (Riverhead Books, 2021)
"A journalist's powerful and incisive account of the forces steering the fate of his sprawling Filipinx-American family reframes how we comprehend the immigrant experience. Nearing the age at which his mother had migrated to the U.S., part of the wave of non-Europeans who arrived after immigration quotas were relaxed in 1965, Albert Samaha began to question the ironclad belief in a better future that had inspired her family to uproot themselves from their birthplace. As a rising tide of inequality and discrimination threatened to engulf her, her brother Spanky-a rising pop star back in Manila, now working as a luggage handler at San Franciso airport, his singing carrying no farther than a restaurant on Fisherman's Wharf-and others of their generation, he wondered whether their decision to abandon a middle-class existence in the Philippines had been worth the cost. Excavating his family's history back to the region's unique geopolitical roots in Spanish colonialism, Japanese occupation, and American intervention, Samaha fits his family's arc into the wider story of global migration as determined by chess moves among superpowers. And by relating their personal history with warmth and affection but also clear-eyed skepticism, 'Concepcion' explores what it might mean to reckon with imperialism's unjust legacy, to live with contradiction and hope, to fight for the unrealized ideals of an inherited homeland"--